The Effect of Adding Gellan Gum to White Rice on the Starch Hydrolysis and Glycemic Index. (7th June 2021) - Alshammari, Norah; Muttakin, Syahrizal; Liu, Qingsu; Gouseti, Ourania; Alyami, Jaber; Lovegrove, Alison; Aithal, Guruprasad P.; Taylor, Moira; Marciani, Luca
Abstract: Objectives: High consumption of starchy foods has been linked to increased risk of type 2 diabetes. Addition of food hydrocolloids gums to food has previously been shown to reduce the digestibility of food. Gellan gum, a polysacchairde produced by sphingomonas eldea is one of many available food hydrocolloid gums. The aim of the present study was to examine the effect of adding gellan gum to white rice during cooking on the starch digestibility and related in-vitro glycemic index(GI). Methods: A static in-vitro digestion model was used based on the protocol from the INFOGEST static in-vitro simulation of gastrointestinal food digestion model (Brodkorb et al, .2019). Four different samples were prepared: (A) Cooked Jasmine rice; (B) Cooked Jasmine rice + 1% low acyl gellan gum, LAGG (KELCOGEL F, CPKelco); (C) Cooked long grain rice and (D) Cooked long grain rice + 1% LAGG. The oral phase was simulated by adding 5 ml of simulated salivary fluid containing human salivary amylase, followed by gastric phase and an intestinal phase. Glucose release was determined by Sugar Reduction Assay(PAHBAH) and compared to a maltose standard curve at consecutive time points for 2 hours. Results: The addition of LAGG inhibited starch hydrolysis for both Jasmine and long grain rice. The greatest effect was observed for Jasmine rice. Starch digestion was reduced with the addition of LAGG to Jasmine rice by 27% and with the addition to long grain rice by 21% at 120 minutes. The GI was calculated using the area under curve and white bread as reference. The addition of LAGG to Jasmine rice reduced the GI value by 8% whilst the effect on long grain rice was less pronounced. Conclusions: The addition of gellan gum to rice during cooking reduced starch digestion in white rice and the in-vitro glycemic index. This might be an effective way to reduce the glycemic response to starchy foods in human. Funding Sources: Ministry of Education, Saudi Arabia Acknowledgment: We thank Neil Cruttenden at CPKelco for the kind gift of gellan gum.